2022
DOI: 10.3390/md20010055
|View full text |Cite
|
Sign up to set email alerts
|

A Promising Potential of Brown Algae Sargassum polycystum as Irreversible Hydrocolloid Impression Material

Abstract: This study aimed to investigate the potential use of brown algae Sargassum polycystum as irreversible hydrocolloid (alginate) impression material. Potassium alginate extracted from Sargassum polycystum was prepared in three different compositions (14%, 15%, and 16%) and mixed with other standard components to form an alginate impression material. Prior to that, the purity of potassium alginate was quantified with Fourier Transform Infrared Spectroscopy (FTIR) analysis. As a control material, the alginate impre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 27 publications
1
8
0
7
Order By: Relevance
“…It was clearly observed that the spray-dried nostoc presented higher intensity for the carboxyl, carbonyl, and hydroxyl functional groups, so it would present an anionic character, which is characteristic of hydrocolloids [ 6 , 52 , 53 , 54 , 55 , 56 ], making it a potential material for use as a food stabilizer [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was clearly observed that the spray-dried nostoc presented higher intensity for the carboxyl, carbonyl, and hydroxyl functional groups, so it would present an anionic character, which is characteristic of hydrocolloids [ 6 , 52 , 53 , 54 , 55 , 56 ], making it a potential material for use as a food stabilizer [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Around 1530 cm −1 , low intensity spectra are observed, corresponding to the stretching vibrations of the COO- and -C=O bonds of the carboxylate anions [ 70 ]; at 1416 cm −1 stretching of the -C-O, -C-H, and -OH single bonds were observed; at 1060 cm −1 a high intensity peak is presented, which would be due to the manifestation of bond stretching -C-O, C-O-C, C-OH, a peak at 815 cm −1 of low intensity that indicates deformation of the -CH 2 bond corresponding to methylene groups, while between 800 and 580 cm −1 different low intensity spectra are presented, this area is known as the “fingerprint” of the materials, these spectra are attributed to stretching of the -C-H and -C-O bonds, belonging to starches and glucose, which is characteristic of hydrocolloids from algae [ 13 , 27 , 70 , 71 , 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the hydrocolloid CH, a peak was observed around 3400 cm −1 , which corresponds to a vibration of the -OH and -NH bond (Figure 3a), characteristic of amides and carboxylic acids, which would allow the establishment of hydrogen bridge bonds; at 2927 cm −1 asymmetric stretching vibrations of the C-H bond are presented, corresponding to the hydrocarbon chains of carbohydrates; another zone with high intensity is found around 1646 cm −1 , it corresponds to a vibration of the stretching of the carbonyl group -C=O, and -OH stretching of the water present, which suggests high hygroscopicity [68,69]. Around 1530 cm −1 , low intensity spectra are observed, corresponding to the stretching vibrations of the COO-and -C=O bonds of the carboxylate anions [70]; at 1416 cm −1 stretching of the -C-O, -C-H, and -OH single bonds were observed; at 1060 cm −1 a high intensity peak is presented, which would be due to the manifestation of bond stretching -C-O, C-O-C, C-OH, a peak at 815 cm −1 of low intensity that indicates deformation of the -CH 2 bond corresponding to methylene groups, while between 800 and 580 cm −1 different low intensity spectra are presented, this area is known as the "fingerprint" of the materials, these spectra are attributed to stretching of the -C-H and -C-O bonds, belonging to starches and glucose, which is characteristic of hydrocolloids from algae [13,27,[70][71][72][73].…”
Section: Ir Analysis Of Composites Subjected To Adsorptionmentioning
confidence: 99%
“…Polimer alginat bersifat hidrofilik yang merupakan molekul linier dengan berat molekul tinggi, mudah sekali menyerap air sehingga senyawa alginat dapat dimanfaatkan sebagai bahan pengemulsi, pengental dan penstabil. 2,16,17 Alginat adalah suatu istilah umum untuk senyawa dalam bentuk garam dan turunan asam alginat. Alginat merupakan polisakarida yang berbentuk gel yang diekstraksi dari alga coklat.…”
Section: Kandungan Alga Coklatunclassified
“…Natrium alginat dan potasium alginat dapat diekstraksi dari spesies alga coklat seperti Sargassum sp., Turbinaria sp., Hormophysa sp., dan Padina sp. 16,17 Sodium alginat adalah salah satu jenis elektrolit molekul makro organik dari spesies rumput laut coklat dengan rumus kimia (C6H7NaO6)n. Sodium alginat dapat larut dalam air dingin atau air panas dan mampu membentuk larutan yang stabil. Sodium alginat digunakan sebagai bahan pembentuk gel dan pengental yang bersifat termoreversibel dalam berbagai bidang industri, dan juga dipakai sebagai suspending emulsifying, dan stabilizing agent.…”
Section: Kandungan Alga Coklatunclassified